International benchmarking for health policy evaluation: the French National Health Strategy. (30th September 2020) - Luciano, L; Low, E; Rey, S; Gaini, M
Abstract: Background: International benchmarking is a valued source of inspiration and learning for policy-makers to develop successful public health policies. Through comparison, the external coherence of one policy can be measured and its objectives redesigned. The French national health strategy (SNS) 2018-2022 comprises the French health policy framework focusing on four priority areas. The aim of this study was to conduct international benchmarking of current national health strategies to explore the external coherence of the SNS and evaluation methods. Methods: A scoping review was conducted through available governmental and public health agencies' websites to survey national/federal health strategies in select high-income countries. Strategical approaches, governance and policy duration were compared with four health priorities of the French SNS: prevention, social/territorial inequalities, quality of care, innovation. A descriptive analysis of these strategies' evaluation methods, including relevant indicators, was executed. Results: Out of 18 countries selected, 11 have a current strategy akin to the four priorities of the French SNS, with a timeline stipulated to implement the policy. The strategies of Australia and Switzerland, out of nine countries with strategies covering these areas, bear the closest resemblance to the French SNS. Evaluation methods varied largely across countries. Conclusions: The majority of countries contain a health strategy with a longer duration compared to the French SNS, irrespective of governance. Similar priorities were found for countries with a national health strategy, with other countries developing at least prevention plans. Most countries provided only partial evaluation methods or overall health target indicators, to be taken into account for the development of the French SNS evaluation plan Key messages: International benchmarking is essential to identify best practices in health policy design. As a result, future French health strategies may benefit from a longer duration of implementation. If great efforts were put in place in France to build a strategy evaluation plan, other countries focused mostly on implementation reports or monitoring national health targets through indicators.